ANTIOXIDANT, ANTIBACTERIAL AND ANTI-INFLAMMATORY POTENTIAL OF THE AQUEOUS EXTRACT OF THE RAW LEAVES OF SRI LANKAN VARIETY OF PERSEA AMERICANA MILLER (AVOCADO) - Deraniyagala Srianthie; Deraniyagala Nilusha Udayangani; Hettiarachchi Chamari (International Journal of Ayurveda and Pharma Research, 2020)
Despite the advances in modern medicine, plant based remedies are currently sought after as alternatives to synthetic drugs. As such natural sources are being searched to use as antioxidants, anti-inflammatory, and antibacterial compounds. This study was focused on the investigation of aqueous leaf extract of Sri Lankan variety of Persea americana (ALEPA) which was prepared according to the method of Kasaya (Decoction) in Ayurvedic medicine to test its antioxidant, anti-inflammatory and antibacterial activities. The total phenolic content of ALEPA was determined by Folin Ciocalteu assay was 681±6.8 mg (PGE) /g (PGE= Pyrogallol equivalents) and the flavonoid content was 1193±302 mg (QE)/g (QE= Quercetin equivalents) according to the AlCl3 colorimetric assay. DPPH radical scavenging activity (RSA) of ALEPA was 11.3±2.8-52.3±5.0% for concentrations of 50-500 µg/ml whereas ascorbic acid showed 28.0±0.7-90.7±0.1% in the concentration range of 200-500 µg/ml. ALEPA showed better ferrous ion reducing activity compared to ascorbic acid. Hydroxyl RSA of ALEPA was 17.4±1.3-41.5±0.5% in the concentration range of 20-50mg/ml whereas ascorbic acid showed 7.0±0.2-19.8±0.5% for the same concentration range. Overproduction of nitric oxide free radicals are implicated in inflammation. In the NO scavenging assay, ALEPA showed activity 26.0±3.6-69.2±2.5% in the concentrations of 0.2-8 ppm whereas ascorbic acid showed activity 26.8±2.5-49.3±1.9% in the concentrations of 0.2-4 ppm. In human red blood cell (HRBC) assay, ALEPA showed 48.0±1.9-60.6±2.6% HRBC membrane protection whereas the Asprin showed 39.7±0.4-49.0±0.5% activity. The prevention of HRBC membrane lysis is taken as a measure of anti-inflammatory activity and also ALEPA showed antibacterial activity towards Escherichia coli, Streptococcus aureus, and Bacillus subtilis.